Course, Moderators, and Predictors of Acute Coronary Syndrome-Induced Post-traumatic Stress: A Secondary Analysis From the Myocardial Infarction-Stress Prevention Intervention Randomized Controlled Trial - von Känel, Roland; Meister-Langraf, Rebecca E.; Barth, Jürgen; Schnyder, Ulrich; Pazhenkottil, Aju P.; Ledermann, Katharina; Schmid, Jean-Paul; Znoj, Hansjörg; Herbert, Claudia; Princip, Mary (Frontiers in Psychiatry, 2021)
Acute coronary syndromes (ACS) induce posttraumatic stress symptoms (PTSS) in one out of eight patients. Effects of preventive interventions, the course and potential moderators of ACS-induced PTSS are vastly understudied. This study explored whether a preventive behavioral intervention leads to a decrease in myocardial infarction (MI)-induced PTSS between two follow-up assessments. Sociodemographic, clinical and psychological factors were additionally tested as both moderators of change over time in PTSS and predictors of PTSS across two follow-ups. Within 48 h after reaching stable circulatory conditions, 104 patients with MI were randomized to a 45-min one-session intervention of either trauma-focused counseling or stress counseling (active control). Sociodemographic, clinical and psychological data were collected at baseline, and PTSS were assessed with the Clinician-Administered Posttraumatic Stress Disorder Scale 3 and 12 months post-MI. PTSS severity showed no change over time from 3 to 12 months post-MI, either in all patients or through the intervention [mean group difference for total PTSS =1.6 (95% CI -1.8, 4.9), re-experiencing symptoms=0.8 (95% CI -0.7, 2.2), avoidance/numbing symptoms=0.1 (95% CI -1.6, 1.7) and hyperarousal symptoms=0.6 (95% CI -0.9, 2.1)]. Patients receiving one preventive session of trauma-focused counseling showed a decrease from 3 to 12 months post-MI in avoidance symptoms with higher age (p=0.011) and direct associations of clinical burden indices with total PTSS across both follow-ups (p’s ≤ 0.043; interaction effects). Regardless of the intervention, decreases in re-experiencing, avoidance and hyperarousal symptoms from 3 to 12 months post-MI occurred respectively in men (p=0.006), participants with low education (p=0.014) and with more acute stress symptoms (p=0.021). Peritraumatic distress (p=0.004) and lifetime depression (p=0.038) predicted total PTSS across both follow-ups. We conclude that PTSS were persistent in the first year after MI and not prevented by an early one-session intervention. A preventive one-session intervention of trauma-focused counseling may be inappropriate for certain subgroups of patients, although this observation needs confirmation. As predictors of the development and persistence of PTSS, sociodemographic and psychological factors could help to identify high-risk patients yet at hospital admission.